Addressing Tipping Points for a Precarious Future (2013)
This book places tipping points in their scientific, economic, governmental, creative, and spiritual contexts. It seeks to offer a comprehensive set of interpretations on the meaning and application of tipping points. Its contribution focuses on the various characterisations and metaphors of tipping points, on the scope for anticipating their onset, the capacity for societal resilience in the face of their impending arrival, and for better ways of communicating and preparing societies, economies, and governments for accommodating them, and hence to turn them into responses which buffer and better human well-being. Above all, the possibility of preparing society for creative and benign ‘tips’ is a unifying theme. The conclusion is sombre but not without hope. Thresholds of profound change can combine earth system-based relatively abrupt shifts with human-caused alterations of these disturbed patterns which, coupled together, produce more rapid onsets and greater tensions and stresses for governments and economies, as well as socially unequal societies. There is still time to predict and address these thresholds but too much delay will make the task of accommodation very difficult to achieve with relevant-scale community support. There are many examples of adaptive resilience throughout the world. These should be identified, supported, and emulated according to cultural acceptance and emerging economic realities. But there is no guarantee that the necessary adjustments can be made in time, as emerging patterns of outlook and governance do not appear to be conducive to manage the very awkward transitions of appropriate response.